"What I wish I had known before starting my PhD". Issue 1 (30th November 2022) - Wiebach, Vincent
Abstract: As a rather recent PhD graduate and still an "early career researcher", the author wondered what to write about that would be interesting for a young scientist. The answer came while overhearing students in the break room stating, "I wish I had known all that before starting my PhD that would have made everything easier!" – An experience many researchers are very familiar with. From simple tricks for laboratory work to choosing the right software or planning the next career steps, this was a reoccurring theme during the career of the author, who will try to give a short personal overview for young researchers, especially in the analytics and/or natural products field. These topics and lists represent a personal opinion and are neither meant to be all‐encompassing nor of course might differ from the experiences of other researchers.